2015
DOI: 10.15283/ijsc.2015.8.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Histological Study on the Therapeutic Effect of Green Tea and Stem Cells in Alzheimer’s Disease Complicating Experimentally Induced Diabetes

Abstract: Background and ObjectivesAlzheimer’s disease (AD) is a devastating neurodegenerative disorder. Increasing evidence implicates diabetes mellitus (DM) as a risk factor for AD. Green tea (GT) has several beneficial effects attributed to its anti-oxidant phenolic compounds. Adipose tissue is a rich source of adipose-derived mesenchymal stem cells (ADSCs). This study was designed to evaluate and compare the possible therapeutic effect of green tea extract (GTE) and ADSCs on AD complicating induced DM in male rat.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…In this study, features of neuronal degeneration and apoptosis detected in H&E stained sections of LPS group were reinforced by the increase in the mean area percent of caspase 3 immunohistochemistry and were in agreement with other research (21). It was reported that oxidative stress is a common mechanism contributing to neuronal damage and apoptosis in neuroinflammatory disorders (22).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, features of neuronal degeneration and apoptosis detected in H&E stained sections of LPS group were reinforced by the increase in the mean area percent of caspase 3 immunohistochemistry and were in agreement with other research (21). It was reported that oxidative stress is a common mechanism contributing to neuronal damage and apoptosis in neuroinflammatory disorders (22).…”
Section: Discussionsupporting
confidence: 93%
“…The acidophilic masses with dark nuclei might represent apoptotic neuronal cells that fuse together and form masses. Pyramidal neurons in EP layer are the principal neurons that mediate many cognitive functions and they appear to be the main substrate for neurodegenerative changes in AD (12). Glial cells increase secondary to the inflammatory process and as an attempt for clearing the degenerated neurons, supported by Nazem et al (16).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained as an attempt of MSC for healing of neurodegeneration, being attracted by inflammatory mediators and products of damaged tissue. The inflammatory mediators and the changes in the microenviroment in AD result in mobilization and differentiation of MSC that can be tissue residents or recruited from the bone marrow (12). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac injury was confirmed as in group II. Four weeks following STZ injection, 0.5 ml of cultured and PKH26-labeled adipose derived mesenchymal stem cells (AMSCs) [12] , obtained from one of the donor's group rats, were suspended in PBS and injected in the tail vein [13] . The injection was performed on two successive days with 24 hours interval [14] .…”
Section: Experimental Designmentioning
confidence: 99%